Toward a Critical Race Theory of Evidence - Gonzales Rose, Jasmine B. (2017)
Scholars, judges, and lawyers have long believed that evidence rules apply equally to all persons regardless of race. This Article challenges this assumption and reveals how evidence law structurally disadvantages people of color. A critical race analysis of stand-your-ground defenses, cross-racial eyewitness misidentifications, and minority flight from racially-targeted police profiling and violence uncovers the existence of a dual-race evidentiary system. This system is reminiscent of nineteenth century race-based witness competency rules that barred people of color from testifying against white people. I deconstruct this problem and introduce the original concept of “racialized reality evidence.” This construct demonstrates how evidence of people of color’s lived experiences of systemic racism are regularly excluded at trial, while evidence of white norms and beliefs receives “implicit judicial notice.” Finally, I advocate for a new critical race theory of evidence law and offer solutions — including a reinterpretation of Federal Rule of Evidence 403 — to increase equality in the courtroom